The evaluation of a new apheresis device for automated red blood cell exchange procedures in patients with sickle cell disease. Issue 4 (21st October 2014) - Quirolo, Keith; Bertolone, Salvatore; Hassell, Kathryn; Howard, Thomas; King, Karen E.; Rhodes, Diane K.; Bill, Jerry
<x xml:space="preserve">Abstract</x> Background The Spectra Optia apheresis system (SO), a blood component separator, can be used to perform red blood cell exchange (RBCX) procedures for the transfusion management of sickle cell disease (SCD) in adults and children. This study was designed to evaluate the performance of the SO RBCX protocols (exchange and depletion/exchange) in patients with SCD. Study Design and Methods Patients with SCD and a need for an RBCX procedure as part of a chronic program or as a single procedure were enrolled in this multicenter, single‐arm, open‐label study. The primary goal of the study was to confirm that the predicted percentage of the patient's original RBCs remaining at the end of the procedure (FCRp) reflects the actual cell fraction remaining, as measured by %HbS (FCRa). Secondary endpoints included ability of the SO to achieve the desired final hematocrit (Hct) and device‐related serious adverse events (SAEs). Results Seventy‐two patients 12 years of age or older were enrolled in the study; 60 were evaluable. The ratio of FCRa to FCRp after the RBCX procedure was 0.90, well within the prespecified range of 0.75 to 1.25. The SO was able to achieve the desired final Hct in the evaluable population. The safety profile was favorable, and no patients had an SAE or unexpected adverse device effect or withdrew from the procedure or treatment due to an adverse event. Conclusion The SO performed effectively and safely for both the RBCX procedure and the RBCX depletion/exchange procedure.